THE VIRTUAL NEUROLOGY EXAMINATION AS A LEARNING TOOL FOR MEDICAL STUDENTS UNDERGOING CLINICAL CLERKSHIPS DURING THE PANDEMIC ERA OF COVID-19 - Pinzon, Rizaldy Taslim; Veronica, Vanessa (Universitas Gadjah Mada, 2023)
Background: Due to the critical importance of the COVID-19 pandemic in the educational system, medical academics must consider safe and appropriate clinical clerkship learning methodologies and models implemented during the pandemic.Aims: This study aimed to construct and evaluate virtual neurology examination as a tool for medical students undergoing clinical clerkships.Learning Media Review: This learning media review was action research conducted at Bethesda Hospital Yogyakarta, Indonesia. This study was conducted in two stages: developing a virtual neurology examination and evaluating student feedback. This study enrolled 12 medical students, the majority of whom were female (58%). The majority of medical students agreed that the virtual neurology assessment was a good overall experience (83%), with the majority stating that the image and sound quality were good (75%) and the virtual neurology examination cases were quite varied (66.5%). Nine medical students (75%) strongly supported the continuation of the virtual neurology examination program, while three medical students (25%) supported its continuation.Conclusion: This study indicates that virtual neurology examination is feasible and can serve as a helpful learning tool for medical students undergoing clinical clerkships during the COVID-19 pandemic.